Evaluation of the Effect of New Multimodal Analgesia Regimen for Cardiac Surgery: A Prospective, Randomized Controlled, Single-Center Clinical Study [Response to Letter] - Jin L; Guo K (Drug Design, Development and Therapy, 2023)
Lin Jin, Kefang Guo Department of Anesthesia, Zhongshan Hospital, Fudan University, Shanghai, People’s Republic of ChinaCorrespondence: Kefang Guo, Department of Anesthesia, Zhongshan Hospital, Fudan University, No. 180, Fenglin Road, Xuhui District, Shanghai, People’s Republic of China, Email dr_guokefang@163.com